IMPLEMENTATION OF ANALYTICAL HIERARCHY PROCESS (AHP) IN DETERMINING CRITERIA FOR NEW HOUSING DEVELOPMENT AND BEST LOCATIONS IN TASIKMALAYA CITY - Nugraha, Muhammad Bisma; Rachman, Andi Nur; Fitriani Dewi, Euis Nur (Deparment Information System, Siliwangi University, 2024)
The growth in the number of households with access to decent and affordable housing in Tasikmalaya City continues to increase. This indicates that housing development in Tasikmalaya City is undergoing significant progress. The criteria for selecting housing vary widely, depending on the priorities of each individual, in line with their expectations for the housing they will live in. These varied choices present challenges for both housing developers and the public in determining the criteria and location of housing. This study aims to develop an information system that can support housing development in new housing projects in Tasikmalaya City. This goal is achieved by creating a Decision Support System (DSS) that considers all housing selection criteria to accelerate and simplify the decision-making process, using the Analytical Hierarchy Process (AHP) method. The research findings indicate that the risk criterion is the highest priority according to the views of stakeholders and the general public, while the design criterion is given the least priority. Information based on selected criteria can be accessed through the